Identifikasi Potensi Perekonomian Wilayah Sekitar Waduk Jatigede - Hazkilla Kanza Pratami; Yulia Asyiawati (UNISBA Press, 2022)
Abstract. The concept of regional development grows due to the need for the region to develop, especially in the availability of natural resources and the increasing needs of the community in line with the increase in population. Jatigede Reservoir is the second largest reservoir in Indonesia, built by damming the Cimanuk River which is found in Sumedang Regency. Jatigede Reservoir has an area of ​​3,053.34 ha which includes 4 sub-districts and 40 villages consisting of Darmaraja District, Wado District, Jatigede District, and Jatigede District. It is stated in Regional Regulation No. 4 of 2018 concerning the RTRW of Sumedang Regency article 42 paragraph 2 letter b as referred to which states that the Jatigede Reservoir is included in the KSK from the point of view of economic growth. The purpose of this study is to determine the potential that can be developed in the area around the Jatigede Reservoir. This study uses a quantitative approach, using regional economic analysis methods, namely, basic economic analysis (LQ), shift share analysis, and Klassen typology analysis. The economy of the area around the Jatigede Reservoir is still quite low. Then the results of the regional economic analysis are obtained, which are obtained from the Klassen typology analysis which produces coffee plantation commodities that can be developed in the area around the Jatigede Reservoir. Abstrak. Konsep pengembangan wilayah tumbuh dikarenakan adanya kebutuhan wilayah untuk berkembang terutama pada ketersediaan sumber daya alam dan adanya kebutuhan masyarakat yang semakin meningkat sejalan dengan adanya pertambahan jumlah penduduk. Waduk Jatigede merupakan waduk terbesar kedua di Indonesia, dibangun dengan membendung aliran sungai cimanuk yang terdapai di Kabupaten Sumedang. Waduk Jatigede memiliki luas sebesar 3.053,34 ha yang mencakup 4 kecamatan dan 40 desa terdiri dari Kecamatan Darmaraja, Kecamatan Wado, Kecamatan Jatinunggal, dan Kecamatan Jatigede. Tercantum dalam Peraturan Daerah No 4 tahun 2018 tentang RTRW Kabupaten Sumedang pasal 42 ayat 2 huruf b sebagaimana dimaksud menyebutkan bahwa Waduk Jatigede termasuk kedalam KSK sudut kepentingan pertumbuhan ekonomi. Tujuan dalam penelitian ini yaitu, untuk mengetahui potensi yang dapat dikembangkan di wilayah sekitar Waduk Jatigede. Penelitian ini menggunakan pendekatan kuantitatif, dengan menggunakan metode analisis ekonomi wilayah yaitu, analisis ekonomi basis (LQ), analisis shift share, dan analisis tipologi klassen. Ekonomi wilayah sekitar Waduk Jatigede masih terbilang cukup rendah. Maka didapatkan hasil analisis ekonomi wilayah, yang didapat dari analisis tipologi klassen yang menghasilkan komoditi perkebunan kopi dapat dikembangkan di wilayah sekitar Waduk Jatigede.